The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/adfm.202009663
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Regeneration through Cyber‐Physical Systems and Microbots

Abstract: Tissue engineering is a systematic approach of assembling cells onto a 3D scaffold to form a functional tissue in the presence of critical growth factors. The scaffolding system guides stem cells through topological, physiochemical, and mechanical cues to differentiate and integrate to form a functional tissue. However, cellular communication during tissue formation taking place in a reactor needs to be understood properly to enable appropriate positioning of the cells in a 3D environment. Hence, sensors and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 151 publications
0
7
0
Order By: Relevance
“…These findings suggest that the remote control of ligandcoupling is cytocompatible and temporally regulates focal adhesion and mechanosensing-mediated potential differentiation of stem cells in vivo, thereby presenting bright prospects for novel dynamic regenerative therapies. [80,81] Approval (KOREA-2021-0006) was obtained from the Institutional Animal Care and Use Committee of Korea University prior to the surgery.…”
Section: Dynamic Control Of Ligand Coupling Temporally Regulates Mech...mentioning
confidence: 99%
“…These findings suggest that the remote control of ligandcoupling is cytocompatible and temporally regulates focal adhesion and mechanosensing-mediated potential differentiation of stem cells in vivo, thereby presenting bright prospects for novel dynamic regenerative therapies. [80,81] Approval (KOREA-2021-0006) was obtained from the Institutional Animal Care and Use Committee of Korea University prior to the surgery.…”
Section: Dynamic Control Of Ligand Coupling Temporally Regulates Mech...mentioning
confidence: 99%
“…Our dynamic manipulation of RGD bridging can elucidate the dynamics of host macrophages interacting with ECM proteins that regulate the integrin receptor recruitment-dependent pro-healing tissue regeneration. [62,63]…”
Section: Research Articlementioning
confidence: 99%
“…[46][47][48] The fluid flow through these scaffolds also causes shear stress known as wall shear stress (WSS), which again acts as a mechanical stimulus. 49 Studies have revealed that the fluid properties, such as velocity and viscosity, affect the cell attachment and proliferation. For example, a scaffold surface subjected to higher WSS under accelerated fluid flow may damage cell attachment, while slow fluid flow may be not sufficient to generate the mechanical stimuli that affect cell proliferation and differentiation.…”
Section: Role Of Scaffold Mechanics On the Mechanobiology Of Cells Or...mentioning
confidence: 99%
“…The use of smart materials that can be employed for designing scaffolds using AM technologies can help in sensing, and simultaneous responding to the cellular microenvironment during tissue development is becoming a reality. 49 With the proper selection of infiltrated material and incorporation of complex and load-bearing geometrical design, hybrid composites of polymers, bioceramics and degradable metals could be the next generation material of choice over the established metallic bone plates, which have the major drawback of a second surgery for the removal of these metallic bio implants. The hybrid composite contains calcium and phosphate ions (known for their osteointegration abilities), which further promotes bone ingrowth.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%